Enhancement of barrier properties using ultrathin hybrid passivation layer for organic light emitting diodes - Bae, Sung Jin; Lee, Joo Won; Park, Jung Soo; Kim, Dong Young; Hwang, Sung Woo; Kim, Jai-Kyeong; Ju, Byeong-Kwon (JAPAN SOC APPLIED PHYSICS, 2006)
The hybrid thin-film (HTF) passivation layer composed of the UV curable acrylate layer and MS-31 (MgO : SiO2 = 3 : 1 wt %) layer was adopted in organic light emitting diode (OLED) to protect organic light emitting materials from penetrations of oxygen and water vapors. The moisture resistance of the deposited HTF layer was measured by the water vapor transmission rate (WVTR). The results showed that the HTF layer possessed a very low WVTR value of lower than 0.007 g/(m(2).day) at 37.8 degrees C and 100% RH. Therefore, the HTF on the OLED was found to be very effective in protect what from the penetrations of oxygen and moisture.